Application of chitosan scaffolds on vascular endothelial growth factor and fibroblast growth factor 2 expressions in tissue engineering principles - Ariyati Retno Pratiwi; Anita Yuliati; Istiati Soepribadi; Maretaningtias Dwi Ariani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Tissue engineering has given satisfactory results as biological tissue substitutes to restore, replace, or regenerate tissues that have a defect. Chitosan is an organic biomaterial often used in the biomedical field. Chitosan has biocompatible, antifungal, and antibacterial properties. Chitosan is osteoconductive, suitable for bone regeneration applications. Bone defect healing begins with inflammatory phase as a response to the presence of vascular injury, so new vascularization is required. Vascular endothelial growth factor (VEGF) and basic fibroblast growth factor-2 (FGF2) are indicators of the beginning of bone regeneration process, playing an important role in angiogenesis. Purpose: This research was aimed to determine the effects of chitosan scaffold application on the expressions of VEGF and FGF2 in tissue engineering principles. Method: Chitosan was dissolved in CH3COOH and NaOH to form a gel. Chitosan gel was then printed in mould to freeze dry for 24 hours. Those rats with defected bones were divided into two groups. Group 1 was the control group which defected bones were not administrated with chitosan scaffolds. Group 2 was the treatment group which defected bones were administrated with chitosan scaffolds. Those rats were sacrificed on day 14. Tissue preparations were made, and then immunohistochemical staining was conducted. Finally, a statistical analysis was conducted using Kruskal Wallis test. Result: There was no significant difference in the expressions of VEGF and FGF2 between the control group and the treatment group (p>0.05). Conclusion: Chitosan scaffolds do not affect the expressions of VEGF and FGF2 during bone regeneration process on day 14 in tissue engineering principles